EFFECT OF PLY ORIENTATION ON ENERGY-ABSORBING CHARACTERISTICS OF COMPOSITE C-CHANNELS SUBJECT TO AXIAL COMPRESSION - FENG ZhenYu; ZHOU Kun; SONG ShanShan; ZHANG XueHan; MOU HaoLei (Jixie qiangdu, 2019)
For three groups of composite T700/MTM28 C-channels with different ply orientation, the load-displacement curves were obtained by axial crushing test. Based on initial peak load, mean crush load, specific energy absorption and crushing efficiency, the effect of ply orientation on crush deformation mode and energy-absorbing characteristics were investigated. The results show that the stable progressive crushing processes are observed during experiments, and various macroscopic failure modes are also presented, such as interlayer cracking, bending fracture, local buckling and shear failure. The [0/90]3 s specimens absorb the largest energy, the [45/90/-45/0]3 specimens absorb the middle energy, while the [45/-45]3 s specimens absorb the smallest energy. The energy-absorbing characteristics can be improved by reasonable design, such as adding 0° plies and 90° plies to ±45° plies.